A new empirical troposphere model using ERA5's monthly averaged hourly dataset. (June 2022) - Dogan, Ali Hasan; Erdogan, Bahattin
Abstract: Due to contents of the dry air and water vapor, troposphere affects radio signals of the space geodetic techniques (e.g., GNSS and VLBI) as range delays. These tropospheric delays should be eliminated to achieve precise point positioning. Over the years, researchers have been developed many of troposphere model. However, the existing models differ from each other in their resolution, data source used and especially in their accuracy. In this paper, a new troposphere model has been presented. The new model considers annual, semi annual and diurnal effects in both sine and cosine form unlike its ancestors. ERA5's monthly averaged hourly dataset has been used to produce the new model. In order to validate new model, the data of ERA5 and terrestrial meteorological stations have been used. Moreover, zenith tropospheric delay (ZTD) values obtained by the new model have been validated by IGS products. Accuracy of the ZTD values has been obtained 3.15 cm. According to the results, it can be concluded that including diurnal effects in both sine and cosine forms improves the accuracies of determined parameters. Highlights: Both surface and pressure level datasets were used. Diurnal effects were considered at the modelling stage. Including both sine and cosine form of annual, semi annual and diurnal effects improves the accuracy of troposphere model.